ESTIMASI ANGKUTAN SEDIMEN MELAYANG DAN KUALITAS AIR SUNGAI DI KAWASAN EKOSISTEM PENTING LAHAN BASAH MASANGAT SUWI KALIMANTAN TIMUR - As, Muli Edwin; Murtinah, Veronika; Bang, Falentino Usat; Sulistyorini, Iin Sumbada; Kusneti, Monica; Isa, Nur Linda (Jurnal Tanah dan Sumberdaya Lahan, 2025)
The Important Ecosystem Area of ​​Mesangat Suwi Wetlands has a total area of ​​around 14,722.69 ha located in East Kutai Regency, East Kalimantan. These wetlands have a strategic role as a regulators of the upstream water system, a source of freshwater fisheries, and a habitat for important protected animals. This study aimed to determine the rate of suspended sediment transport and river water quality. The study was conducted in two stages, the first was data and sample collection in the field, and the second was laboratory testing. The results of the study showed that the river water discharge and TSS in the Suwi and Masangat Rivers at the study location were directly proportional to the height of suspended sediment. The total average of suspended sediment in Suwi was smaller, it's 0.79 tons/year compared to Masangat at 2.64 tons/year. suspended sediment grains could settle and become bottom sediment. The rate of sedimentation in the river would accelerate the shallowing process which affected the wetlands ecosystem. The reduction in vegetated or forested areas in the Masangat wetlands was due to high human activity compared to Suwi. Currently, the water quality in the study areas, including COD, BOD, TDS, and TSS, is generally still below the standard quality threshold and is categorized as class two, namely water that can be used for freshwater fish farming, recreational facilities, livestock farming, and can be used to irrigate crops or rice fields.